Security Model for Tracking Creation of Mobile Money Using Transport Layer Security Protocol - Rwiza, Sigsbert; Kissaka, Mussa; Kapis, Kosmas (Tanzania Journal of Science, 2020)
Mobile Network Operator (MNO) financial service model has security vulnerabilities in addressing verification of cash and mobile money. For instance, monthly returns are transferred in plain text from banks and MNOs to financial regulators. This may result to failure of financial regulators in detecting creation of fake mobile money. This study was conducted to develop a security model for tracking creation of mobile money using Transport Layer security protocol as a way of protecting returns in transit from banks and MNOs to financial regulators. The proposed model was developed using insights from literature, function decomposition and composition techniques and was tested by prototyping the system for tracking creation of mobile money using Laravel PhP framework, apache webserver, JavaScript Object Notation (JSON) server and PhP programming language. The proposed model has eight components, namely; certificate authority, financial regulator server, bank server, MNO server, bank system, mobile money system, super-agent and mobile money issuer components.